Holographic anniversaries: a tribute to holographic pioneers - Kujawińska, Małgorzata (Photonics Letters of Poland, 2021)
This editorial presents shortly the holographic timeline and the most important holographic pioneers. This is the background to an overview of the contents of this special volume of the Photonics Letters of Poland, devoted mainly to digital holography. The published papers from international research groups present a wide range of approaches and applications including metrology, displays, computer-generated holograms, and biomedicine.